1998
DOI: 10.1086/302100
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Microdeletions Spanning the Diamond-Blackfan Anemia Locus on 19q13 and Evidence for Genetic Heterogeneity

Abstract: Diamond-Blackfan anemia (DBA) is a rare pure red-cell hypoplasia of unknown etiology and pathogenesis. A major DBA locus has previously been localized to chromosome 19q13.2. Samples from additional families have been collected to identify key recombinations, microdeletions, and the possibility of heterogeneity for the disorder. In total, 29 multiplex DBA families and 50 families that comprise sporadic DBA cases have been analyzed with polymorphic 19q13 markers, including a newly identified short-tandem repeat … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
55
0

Year Published

2001
2001
2013
2013

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 68 publications
(61 citation statements)
references
References 22 publications
6
55
0
Order By: Relevance
“…8,9 However, mutations of the RPS19 gene have only been identified in 25% of cases, 8,10 suggesting a greater degree of genetic heterogeneity than expected from the initial linkage studies. 7,11 In this report we provide evidence for the existence of a second DBA gene on chromosome 8p, and also for further genetic heterogeneity.…”
Section: Introductionsupporting
confidence: 51%
See 1 more Smart Citation
“…8,9 However, mutations of the RPS19 gene have only been identified in 25% of cases, 8,10 suggesting a greater degree of genetic heterogeneity than expected from the initial linkage studies. 7,11 In this report we provide evidence for the existence of a second DBA gene on chromosome 8p, and also for further genetic heterogeneity.…”
Section: Introductionsupporting
confidence: 51%
“…1,[4][5][6] Recently, linkage analysis of 29 European families showed that DBA in 26 of both dominant and recessive families mapped to chromosome 19q. 7 Identification of a patient with a translocation led to the cloning of a gene on chromosome 19q13.2 that encodes a ribosomal protein, RPS19. 8,9 However, mutations of the RPS19 gene have only been identified in 25% of cases, 8,10 suggesting a greater degree of genetic heterogeneity than expected from the initial linkage studies.…”
Section: Introductionmentioning
confidence: 99%
“…Microdeletions in 19q13.2 have been associated with mental retardation, skeletal malformations, and DiamondBlackfan anaemia. [128][129][130] This suggests a contiguous gene syndrome which includes the ribosomal protein S19 that is mutated in Diamond-Blackfan anaemia.…”
Section: Qmentioning
confidence: 99%
“…3,[15][16][17][18] Recently, a balanced translocation (X;19) was identified in a patient with DBA and the translocation breakpoint was shown to disrupt the ribosomal protein S19 (RPS19) gene. 8,19,20 Subsequent analysis of the RPS19 gene revealed mutations in a subset of patients with DBA. Heterozygous mutations in the RPS19 gene have to date been found in approximately 25% of patients with DBA and families with a history of DBA, including nonsense, frameshift, splice site, and missense mutations.…”
Section: Introductionmentioning
confidence: 99%
“…5,6 Most of the reported cases of DBA are sporadic but 10% to 25% have a positive family history. 7,8 Seventy percent of patients respond initially to corticosteroid treatment, 2,9 but 40% become transfusion-dependent. 9 Allogeneic bone marrow transplantation has been shown to be an effective cure for the disease, which demonstrates that the cause of the disease is intrinsic to the bone marrow.…”
mentioning
confidence: 99%